Casanova y la mujer sin rostro : un caso del comisario de las muertes extrañas - Barde-Cabuçon, Olivier (Nuevos tiempos (Madrid, Spain), 2014)
Paris, 1759: Just a couple of years before the young Volnay, despite its little sympathy for the monarchy, Louis XV saved from death in the attack by Damiens, and thanked the king created for him the post of commissioner of the strange deaths.